One-year outcome of a prospective trial stopping dual antiplatelet therapy at 3 months after everolimus-eluting cobalt-chromium stent implantation: ShortT and OPtimal duration of Dual AntiPlatelet Therapy after everolimus-eluting cobalt-chromium stent (STOPDAPT) trial - Natsuaki, Masahiro (Cardiovasc Interv Ther, 2015)
There has been no previous prospective study evaluating dual antiplatelet therapy (DAPT) duration shorter than 6 months after cobalt-chromium everolimus-eluting stent (CoCr-EES) implantation. STOPDAPT trial is a prospective multi-center single-arm study evaluating 3-month DAPT duration after CoCr-EES implantation. The primary endpoint was a composite of cardiovascular death, myocardial infarction (MI), stroke, definite stent thrombosis (ST) and TIMI major/minor bleeding at 1 year. Between September 2012 and October 2013, a total of 1525 patients were enrolled from 58 Japanese centers, with complete 1-year follow-up in 1519 patients (99.6 %). Thienopyridine was discontinued within 4 months in 1444 patients (94.7 %). The event rates beyond 3 months were very low (cardiovascular death: 0.5 %, MI: 0.1 %, ST: 0 %, stroke: 0.7 %, and TIMI major/minor bleeding: 0.8 %). Cumulative 1-year incidence of the primary endpoint was 2.8 % [upper 97.5 % confidence interval (CI) 3.6 %], which was lower than the pre-defined performance goal of 6.6 % (P < 0.0001). Using the CoCr-EES group in the RESET trial as a historical comparison group, where nearly 90 % of patients had continued DAPT at 1 year, cumulative incidence of the primary endpoint tended to be lower in the STOPDAPT than in the RESET (2.8 versus 4.0 %, P = 0.06) and adjusted hazard ratio was 0.64 (95 % CI 0.42–0.95, P = 0.03). The cumulative incidence of definite/probable ST was lower in the STOPDAPT than in the RESET [0 patient (0 %) versus 5 patients (0.3 %), P = 0.03]. In conclusion, stopping DAPT at 3 months in selected patients after CoCr-EES implantation was at least as safe as the prolonged DAPT regimen adopted in the historical control group. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12928-015-0366-9) contains supplementary material, which is available to authorized users.